2014
DOI: 10.1109/tnsre.2013.2291907
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and Classification of Gait Cycles

Abstract: Gait abnormalities can be studied by means of instrumented gait analysis. Foot-switches are useful to study the foot-floor contact and for timing the gait phases in many gait disorders, provided that a reliable foot-switch signal may be collected. Considering long walks allows reducing the intra-subject variability, but requires automatic and user-independent methods to analyze a large number of gait cycles. The aim of this work is to describe and validate an algorithm for the segmentation of the foot-switch s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
117
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 16 publications
1
117
0
Order By: Relevance
“…= 0.5 is chosen for normalized data and achieves satisfactory performance [4] (for this experiment, the datasets are normalized from 0 to 1 in magnitude). But it may not always be the optimal segmentation value …”
Section: Usuallymentioning
confidence: 99%
See 2 more Smart Citations
“…= 0.5 is chosen for normalized data and achieves satisfactory performance [4] (for this experiment, the datasets are normalized from 0 to 1 in magnitude). But it may not always be the optimal segmentation value …”
Section: Usuallymentioning
confidence: 99%
“…As a newly developed research area, gait analysis has shown great potential for diagnosis in neurodegenerative diseases such as Parkinson's disease or peripheral neuropathy. Different systems are used in order to obtain gait signals, such as vision-based systems [1], goniometers [2], Inertial Measurement Units (IMUs) [3], foot pressure sensors [4]. Gait data are commonly recorded at different parts of human body, such as lower limbs, feet, and lower waist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gait events can be detected using either force based measurement systems by means of footswitches such as force sensitive resistors (FSR) [4], or wearable sensor such as Inertia Measurement Unit (IMU) [5]. To perform outdoor activities for longer period of time, it is crucial to use the systems which are reliable, portable, small, inexpensive, and with low power consumption [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with pathologic gait suffer from higher energy consumption and risk of falls. Gait analysis and event detection has been used in different applications using ambulatory gait systems to evaluate and improve patients' motilities and to control the functional electrical stimulation (FES) [1][2][3].Gait events can be detected using either force based measurement systems by means of footswitches such as force sensitive resistors (FSR) [4], or wearable sensor such as Inertia Measurement Unit (IMU) [5]. To perform outdoor activities for longer period of time, it is crucial to use the systems which are reliable, portable, small, inexpensive, and with low power consumption [6][7][8].…”
mentioning
confidence: 99%